English Teacher’s Challenges in Implementing ‘Joyful Learning’ Method an Indonesian Junior High School - Hikmat, Mauly Halwat; Zahra, Shabrina Zulfati Az (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to identify the overall Joyful Learning method that has been implemented by English teachers in the current Merdeka Curriculum. This research also aims to analyze the challenges faced by teachers, and evaluate students' responses to the application of this teaching method in class. Methodology: The methodology used in the research of Joyful Learning method in junior high school is semi-structured interviews and school observation, which are used to collect data using a qualitative research approach. Results: The/results/of the data obtained by the researcher, show that with the application of the Joyful Learning method in class learning has succeeded in making the percentage of students interested in learning foreign languages increase, so that students can easily learn English language material at the next school level. Applications/Originality/Value: however, as for the challenges or obstacles that teachers have in applying this method, teachers have their own ways so that learning runs well and smoothly. To provide assistance to students in understanding the material provided by the teacher, then the challenges faced by teachers can be resolved with this research. teachers can focus more on the methods that should be used to suit students' abilities. The results of this study add to our understanding of English language teaching methods at the junior high school level and provide guidance to improve the effectiveness of the Joyful Learning method.